2013
DOI: 10.4236/fns.2013.48a013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Homogenization Temperature and Pressure on Lipoprotein Lipase Activity and Free Fatty Acids Accumulation in Milk

Abstract: This study demonstrated that homogenization did not increase the activity of lipoprotein lipase (LPL) in spite of a fast accumulation of free fatty acids (FFA). Two homogenization pressures (100 and 170 bar) and two temperatures (40and 50) were examined. The activity of LPL was analyzed and the formation of FFA was measured with two different methods, the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…In the present study, increasing homogenization temperature led to a decrease in the D [4,3] and D [3,2] values and an increase in the specific surface area values of the milk. Similar to our results, Wiking and Dickow (2013) found that D [4,3] value of fat globules decreased by approximately 14%, when homogenization temperature of milk increased from 40 °C to 50 °C at 10 MPa, and the authors explained that decrease in viscosity of milk with increasing the homogenization temperature might cause the milk fat globules to become smaller due to the potentiating effect of homogenization at high temperature.…”
Section: Resultssupporting
confidence: 90%
“…In the present study, increasing homogenization temperature led to a decrease in the D [4,3] and D [3,2] values and an increase in the specific surface area values of the milk. Similar to our results, Wiking and Dickow (2013) found that D [4,3] value of fat globules decreased by approximately 14%, when homogenization temperature of milk increased from 40 °C to 50 °C at 10 MPa, and the authors explained that decrease in viscosity of milk with increasing the homogenization temperature might cause the milk fat globules to become smaller due to the potentiating effect of homogenization at high temperature.…”
Section: Resultssupporting
confidence: 90%
“…This finding indicated the dominant role of thermal effects of UST treatment on lipase activity. In earlier studies where homogenization was performed at lesser pressures of 200 MPa (Datta et al, 2005) and 17 MPa (Wiking and Dickow, 2013), the lipase activity was observed to be reduced by increasing temperature. In the present study conducted at 400 MPa, the lipase activity of samples UST treated at 35°C were lesser than 65°C UST-treated samples.…”
Section: Effect Of Various Treatments On Milk Quality Attributesmentioning
confidence: 91%